2019
DOI: 10.1001/jama.2019.11825
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Vitamin C Infusion on Organ Failure and Biomarkers of Inflammation and Vascular Injury in Patients With Sepsis and Severe Acute Respiratory Failure

Abstract: IMPORTANCE Experimental data suggest that intravenous vitamin C may attenuate inflammation and vascular injury associated with sepsis and acute respiratory distress syndrome (ARDS).OBJECTIVE To determine the effect of intravenous vitamin C infusion on organ failure scores and biological markers of inflammation and vascular injury in patients with sepsis and ARDS. DESIGN, SETTING, AND PARTICIPANTSThe CITRIS-ALI trial was a randomized, double-blind, placebo-controlled, multicenter trial conducted in 7 medical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
766
2
26

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 696 publications
(809 citation statements)
references
References 32 publications
(61 reference statements)
15
766
2
26
Order By: Relevance
“…We identified nine trials satisfying our selection criteria [11][12][13][14][15][16][17][18][19]. We did not include two further trials that reported "ventilator-free days" since we were unable to convert this to our outcome of interest, "duration of mechanical ventilation" [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…We identified nine trials satisfying our selection criteria [11][12][13][14][15][16][17][18][19]. We did not include two further trials that reported "ventilator-free days" since we were unable to convert this to our outcome of interest, "duration of mechanical ventilation" [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…10 Rescue therapy with high-dose vitamin C can also be considered. 11 Finally, ECMO should be considered using the inclusion and exclusion criteria of the EOLIA trial. 3 Since treatment of severe ARDS from COVID-19 is an ongoing challenge, it is important to learn from the patients who have been treated to gain an understanding of the disease's epidemiology, biological mechanisms, and the effects of new pharmacological interventions.…”
Section: Therapy Implementationmentioning
confidence: 99%
“…(secondary outcome) (284). The rationale for glucocorticoid treatment in association with high dose ascorbic acid was the subject of recent reviews (237,267).…”
Section: Vitamin Cmentioning
confidence: 99%